2015
DOI: 10.1080/23744731.2015.1015382
|View full text |Cite
|
Sign up to set email alerts
|

Integration of an adsorption chiller in an open-cycle desiccant-assisted air-conditioning system

Abstract: In a pilot installation at Hamburg University of Technology, the coupled operation of an open-cycle desiccant-assisted air-conditioning system with an adsorption chiller in combination with cooling ceilings to remove sensible loads is investigated. This article presents experimental results of the year 2013 with a special focus on the performance of the adsorption chiller. Furthermore, the system is compared to two reference systems relying on vapor compression chillers. The average thermal coefficient of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The air-handling unit is designed as a hybrid system, similar to the facility presented in [25]. The outdoor air is dehumidified in a desiccant wheel (1-2) and precooled by the sensible heat regenerator (2)(3).…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The air-handling unit is designed as a hybrid system, similar to the facility presented in [25]. The outdoor air is dehumidified in a desiccant wheel (1-2) and precooled by the sensible heat regenerator (2)(3).…”
Section: System Descriptionmentioning
confidence: 99%
“…Fong et al [24] proposed and simulated the coupling of a desiccant assisted air handling unit to a closed cycle adsorption chiller. In [25] such a system was investigated experimentally. The study showed that considerable primary energy savings are possible depending on the heat generation processes.…”
Section: Introductionmentioning
confidence: 98%